Fluorinated Boron Nitride Quantum Dots: A New 0D Material for Energy Conversion and Detection of Cellular Metabolism. (18th December 2018) - Radhakrishnan, Sruthi; Park, Jun Hyoung; Neupane, Ram; de los Reyes, Carlos A.; Sudeep, Parambath M.; Paulose, Maggie; Martí, Angel A.; Tiwary, Chandra Sekhar; Khabashesku, Valery N.; Varghese, Oomman K.; Kaipparettu, Benny Abraham; Ajayan, Pulickel M.
Abstract: Quantum dots encompass a broad spectrum of optical, catalytic, and electrochemical properties bringing in novel applications in catalysis, imaging, displays, and optoelectronics. Herein, the unanticipated broad‐spectrum light absorption and high fluorescence quantum yield in fluorinated boron nitride (FBN) quantum dots are discussed. A heterostructure of FBN quantum dots with a wide‐bandgap semiconductor, titania nanotube arrays, exhibits high photocatalytic activity as evidenced by high external quantum efficiency extending from ultraviolet to green region of the solar spectrum (≈24% at 400 nm). The high activity is confirmed using photoelectrochemical hydrogen evolution experiments. Further, it is demonstrated that high fluorescence quantum yield could be tapped for the detection of glycolytic activity in cancer cells compared to normal cells. This finding could shift the paradigm of molecular detection using quantum dots. The 0D structure and the gap states introduced through fluorination are believed to be responsible for these unprecedented characteristics of boron nitride. Abstract : The synthesis and characterization of the novel material, fluorinated boron nitride quantum dots, are described at length here along with its application in photocatalysis and detection of cancer cells. As a cocatalyst with titania nanotubes, it enhances the photocatalytic activity in the visible region. Optical properties of quantum dots enable the detection of cancer cells with simple laboratory‐scale technique.